Challenges and Results of Laparoscopic Splenectomy for Hematological Diseases in a Developing Country. (1st August 2018) - Shakya, Vikal Chandra; Byanjankar, Bikram; Pandit, Rabin; Pangeni, Anang; Shrestha, Anir Ram Moh; Poudyal, Bishesh
Abstract : Introduction . Though, in developed countries, laparoscopy is now a gold standard for splenectomy, we are lacking in this aspect in the eastern world. Splenectomy has mostly been performed by open surgery in our region. This is our effort to introduce laparoscopic splenectomy in our country. Methods . This is a retrospective cohort study done in patients presenting to hematology and surgery department of our hospital who underwent laparoscopic splenectomy for hematological diseases from January 2013 to December 2016. Results . There were 50 patients (38 females, 12 males). The diagnoses were idiopathic thrombocytopenic purpura in 31, (steroid/azathioprine-resistant, steroid dependent), hereditary spherocytosis in 9, alpha-thalassemia in 3, beta-thalassemia in 2, autoimmune hemolytic anemia in 4, and isolated splenic tuberculosis in 1. Average platelet counts preoperatively were62000 ± 11000 /mm3 (range 52000-325000/mm3). The mean operative time was130 ± 49 minutes (range 108-224 min). The mean postoperative stay was4 ± 2.11 days (range 3-9 days). Laparoscopic splenectomy could be completed in 45 (90%) patients. Conclusion . Laparoscopic splenectomy could be successfully contemplated in patients with hematological diseases, especially if spleen is normal or only mildly enlarged, and is an advantageous alternative to open splenectomy. Absence of ideal resources has not limited our progress in minimal access approach.